2000
DOI: 10.1103/physrevb.62.5331
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic contributions to spin-wave damping and renormalization in thinNi50Fe50films

Abstract: Ferromagnetic resonance has been used to study the room-temperature linewidth and frequency shift of the qϭ0 spin-wave mode in thin films of NiFe sputtered on Si͑100͒ substrates. The data on the variation of the linewidth and resonance field with film thickness are completely consistent with the extrinsic mechanism recently proposed by Arias and Mills based on momentum nonconserving two-magnon scattering off defects on the film surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 12 publications
8
56
1
Order By: Relevance
“…They showed that lateral variations in the perpendicular uniaxial interface anisotropy field ͑due to the interface roughness͒ are a leading source of the two magnon scattering in ultrathin films. Azevedo et al 16 found in Ni 50 Fe 50 sputtered films that the measured variations of the FMR linewidth and field were consistent with the two magnon scattering model proposed by Arias and Mills.…”
Section: Introductionsupporting
confidence: 61%
“…They showed that lateral variations in the perpendicular uniaxial interface anisotropy field ͑due to the interface roughness͒ are a leading source of the two magnon scattering in ultrathin films. Azevedo et al 16 found in Ni 50 Fe 50 sputtered films that the measured variations of the FMR linewidth and field were consistent with the two magnon scattering model proposed by Arias and Mills.…”
Section: Introductionsupporting
confidence: 61%
“…2(a)]. The large effective intrinsic damping α 0 in our samples can be understood in terms of efficient two-magnon scattering induced by roughness in thin ferromagnetic films [33,34], especially when magnetized in the film plane [35].…”
Section: A In-plane Measurements and Simulationsmentioning
confidence: 99%
“…Our predictions seem confirmed by recent experiments. 7 One can inquire if the two magnon mechanism is operative in nanowires as well.…”
Section: Discussionmentioning
confidence: 99%
“…This will lead to extrinsic contributions to the ferromagnetic resonance linewidth similar to those demonstrated to be substantial in ultrathin ferromagnetic films. 7 Also, when the ferromagnetic resonance mode of the nanowire is excited, the precession of the magnetization leads to large magnetic fields outside the sample, in contrast to the case of thin films, where the field is confined to the film interior. There should then be strong interactions between nanowires, in dense arrays such as those explored by Ebels and Wigen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation